Optimization of Timetables on the Bratislava–Žilina–Košice Route in the Period after the End of the COVID-19 Pandemic - Dedík, Milan; Zitrický, Vladislav; Valla, Michal; Gašparík, Jozef; Figlus, Tomasz (Sustainability, 2022)
Quality and efficient long-distance transport as a key system of public passenger transport could be the basis for the national and international comprehensive integrated transport system. Especially due to the pandemic caused by the COVID-19 disease, the demand for long-distance transport has significantly decreased since March 2020 in the Slovak Republic on the busiest long-distance line Bratislava–Žilina–Košice. It is, therefore, necessary to propose various measures in order to increase this demand and bring passenger frequencies to at least the level of values before this period. This paper analyzes the impact of the measures on passenger frequencies in 2020, examining the amount of their fall in individual months of the first half of the year 2020 on the long-distance route Bratislava–Žilina–Košice. Furthermore, the paper deals with the long-term concept of national long-distance passenger rail transport on the mentioned line in the period after the end of the pandemic. It uses scientific methods enabling to rationalize and optimize current train timetables. The benefits of these proposals will be to offer passengers better transport services, with their frequencies expected to increase in the coming years.